Engineering structure and functionalities of chemical vapor deposited photocatalytic titanium dioxide films through different types of precursors. Issue 20 (26th April 2021) - Samélor, Diane; Turgambaeva, Asiya; Krisyuk, Vladislav; Miquelot, Adeline; Cure, Jeremy; Sysoev, Sergey; Trubin, Sergey; Stabnikov, Pavel; Esvan, Jérôme; Constandoudis, Vassilios; Vahlas, Constantin
Abstract : The functional properties of photocatalytic CVD processed TiO2 films can be monitored by appropriately selecting the precursors chemistry. Abstract : The photocatalytic properties of titanium dioxide TiO2 thin films, a seminal semiconductor material in solar radiation involving key enabling technologies depend on their structural characteristics which, in turn are monitored by the type and the conditions of the applied deposition technique. In this work, we investigate the physicochemical characteristics of two solid precursors, oxo-β-diketonate TiO(thd)2 (1 ) and mixed alkoxide-β-diketonate Ti(thd)2 (OBu)2 (2 ), for the chemical vapor deposition (CVD) of TiO2 films as alternatives to the established liquid titanium(iv ) isopropoxide (TTIP). We show that vaporization of 1 results in a complex mixture of intermediate species, while that of 2 occurs congruently. Direct liquid injection CVD from 1, 2, and TTIP at 500 °C results in anatase containing, rutile rich two phase films for the first two, and to pure anatase for the latter. Films deposited from 1 and 2 are composed of large grains with limited porosity, with smaller and more densely packed aggregates for the former, which also presents a higher O/Ti ratio in the O–Ti lattice. These differences account for a higher generation rate of H2 of films from 1, in the photocatalytic decomposition of water. This comparative experimental information can be useful to build new models for extended and more reliable predictions in a materials by design approach.